Palladium-catalyzed Sonogashira coupling reactions in γ-valerolactone-based ionic liquids - Orha, László; Tukacs, József M.; Kollár, László; Mika, László T. (Beilstein Journal of Organic Chemistry, 2019)
It was demonstrated that the γ-valerolactone-based ionic liquid, tetrabutylphosphonium 4-ethoxyvalerate as a partially bio-based solvent can be utilized as alternative reaction medium for copper- and auxiliary base-free Pd-catalyzed Sonogashira coupling reactions of aryl iodides and functionalized acetylenes under mild conditions. Twenty-two cross-coupling products were isolated with good to excellent yields (72–99%) and purity (>98%). These results represent an example which proves that biomass-derived safer solvents can be utilized efficiently in common, industrially important transformations exhibiting higher chemical and environmental efficiency.
Keywords: catalysis; cross coupling; green chemistry; ionic liquids